Karel Hynek Mácha v iniciačním procesu - Václavů, Kateřina (Lidé města, 2006)
I have borrowed the notion of “initiatory process” from anthropology, however I do not feel it is necessary to describe it in detail here. These are land mark, transitional and dangerous periods that manifest themselves in probably every human live, when something old dies and something new is born. Child turns into a girl, changes into a woman, gets married, becomes a mother, dies and becomes an ancestor. Child turns into a boy, changes into a man, maybe an important man in his community, dies and becomes an ancestor. The above “becomes” and “changes” is just that initiatory period, trial and transition, that can be managed or mismanaged by infinitely human manners, however in a single direction, only. Such a simple circuit with endless number of variations. You kill the biggest bison, kill the most enemies, save a friend, become top model, publish your first book, start taking drugs and get over it. And yes, the biggest fight, the one that remains always the same and does not have to manifest itself at all in outer world as a heroic act, is surely awaiting someplace deep inside. Deep inside where something is blinking and it is so difficult to see - hear and keep in plain sight, where all questions and answers await closely tied together. When he was about 25 years old, Karel Hynek Mácha also entered his inner field and suddenly the earth started to shake under his feet. And here I enter and so does my eye yearning so much to see how new temples of live are built, my eye in my head that just wants to nod in agreement when reading his poetry. However, Mácha dies at the age of twenty six (and now we can start speculate what was the physical cause - germs, virus - typhus, cholera, stomach flu - who knows -), after he published his first compact work and just a few days before his planned wedding. He leaves behind only his adolescent poetry and his diaries that sometimes make my head just marvel motionlessly.